Penerapan Ketentuan Kesehatan Awak Kapal Berdasarkan Maritime Labour Convention 2006: Studi Kasus di PT Meratus Line Surabaya - Hildan Nauril Azhar; Christine Widilestari; Fajar Sari Kurniawan; Widanto Mukti Adi (PPPM Polimarin, 2025)
This study aims to determine the implementation of ship crew health standards based on the 2006 Maritime Labor Convention at PT Meratus Line Surabaya and identify the obstacles faced. The 2006 Maritime Labor Convention is an international convention that regulates work standards and the welfare of seafarers, including health aspects that include comprehensive health checks before crews serve on board ships. This study uses a qualitative approach with data collection methods through observation, in-depth interviews, and documentation. The results show that PT Meratus Line has carried out comprehensive Medical Check Up (MCU) examinations before crews on board, and issued health certificates according to the 2010 STCW standards. However, the implementation still faces various obstacles such as the limited number of competent medical personnel on board and the presence of prospective crew members who are declared unfit for duty due to health conditions. To overcome this, the company provides basic medical training to ship officers, provides medical facilities to crew members who are unfit for duty, and conducts regular health monitoring. In conclusion, although the implementation has been carried out in accordance with the provisions of the 2006 Maritime Labor Convention, it is still necessary to improve periodic evaluations and strengthen the training system to achieve optimal and sustainable ship crew health stan